Itin[errância] - Oliveira, Andreia Machado (Contemporânea - Revista do PPGART/UFSM, 2019)
Itin[errância] Andreia Oliveira Vídeo projeção 03:54 2019 Design de áudio Luiz Augusto Alvim Produção LabInter